Text Writing within Simple Sentences: A Writing Fluency Intervention for Students with High‐Incidence Disabilities. Issue 1 (4th October 2018) - Datchuk, Shawn M.; Rodgers, Derek B.
Abstract: Good sentence construction, the act of writing multiple words into sentence types that make semantic and syntactic sense, is needed for clear and meaningful written expression. The present study investigated the effects of a multi‐component writing intervention, sentence instruction and frequency building to a performance criterion, on the simple sentence construction of intermediate‐grade level students with high‐incidence disabilities. Four special education teachers delivered intervention to small groups of two students, a total of eight students, and assessed for retention. Overall results were positive but inconsistent across the small groups. Three of the four small groups improved their text writing within simple sentences during and following intervention, and moderate to large Tau‐ U values for correct word sequences and for incorrect word sequences, respectively, were found. Results suggest that postinstruction writing fluency practice can be an effective part of writing intervention for intermediate‐grade level students with high‐incidence disabilities.